The Impact of Pay Reform on the Organizational Performance (A Case Study: Implementation of Remuneration at Universitas Padjadjaran) - Ira Irawati; Nunung Runiawati; Imanudin Kudus (Jurnal Ilmu Pemerintahan Widya Praja, 2017)
Unpad needs a new payment system as the demand in improving the performance and legality of compensation payment based on the level of responsibility and the needed demand of professionalism. By proposing the principle of pay for performance, since 2015 Unpad has conducted pay reform known as remuneration. Meanwhile, the purpose of remuneration system at Unpad is to obtain human resources with the appropriate qualification so that it makes sure that they work professionally, retains good and high achieving employees, motivates employees to work productively, gives rewards to employees based on their performance and work achievements, and controls the employee cost. This paper would explain how pay reform affects the performance of Unpad, particularly in achieving tridharma perguruan tinggi (the three obligations of universities). The research method applied was the qualitative with collection data techniques of participatory observation, interviews, and literatur review. The research result showed that the implementation of pay reform which has been conducted by Unpad since 2015 has a significant impact on the improvement of organizational performance, especially tridharma perguruan tinggi (the three obligations of universities). It is because besides the principle of pay for performance, the implementation of remuneration also refers to the principle of pay for position and pay for people.